Determination of bacteria and fungi in fresh alpaca semen obtained by three collection techniques - Pacheco Curie, Joel I. (2022)
The study aimed to describe the microbiota present in alpaca semen. Fifteen semen samples were collected using the artificial vagina, electroejaculation and post-copula techniques (five per technique). In addition, preputial (n=5) and vaginal (n=5) swabs were made. Microbiological cultures were made to determine the bacterial and fungal genera and an assessment of the bacterial load by determining the number of colony-forming units (CFU/ml). Six bacterial genera were identified in the vagina and seven in the prepuce, in addition to a fungal species (Aspergillus fumigatus). Bacteria of the genera Escherichia, Staphylococcus, Streptococcus and Bacillus were the most abundant and present in semen obtained by the three techniques, coinciding with those found in preputial and vaginal swabs. The amount of CFU/ml was similar for the three techniques, while there was no presence of fungi in the semen obtained by electroejaculation, probably due to the previous preputial washing. The presence and quantity of bacterial and fungal genera was higher than that reported in other animal species.